ENVIRONMENTAL FACTORS AFFECTING PRODUCTIVITY OF TWO INDONESIAN VARIETIES OF BLACK PEPPER (Piper nigrum L.) - Yudiyanto, Yudiyanto; Rizali, Akhmad; Munif, Abdul; Setiadi, Dede; Qayim, Ibnul (AGRIVITA Journal of Agricultural Science, 2014)
Black pepper plantation area in Lampung province (the biggest producer area within Indonesia) has decreased from time to time, which might be related to unfavourable environmental condition. The aim of this study was to assess which environmental factors are positively or negatively correlated with productivity in particular yield of two local varieties of black pepper plant (Natar 1 and Natar 2) in Lampung province.  Two observational studies were carried out in the present study i.e. phenological development and productivity of black pepper productivity in related to various environmental factors. Our results showed that productivity of two varieties were significantly affected rainfall, light intensity and micro humidity. Dry matter yield was positively correlated with rainfall, both in Natar 1 and Natar 2. It was concluded that among environmental factors affecting productivity of black pepper, rainfall intensity was the most influencing factor with a positive relationship with the productivity.Keywords: Black pepper, climate, cultivar, environment, Indonesia